Bandongan and Sorogan as Epistemic Practices : Reconstructing Islamic Literacy beyond Cognitive Formalism - Aisyah Siti; Nuryadin Nuryadin; Asikin Nor; Ibnu Arabi; Muhammad Nur Effendi (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2026)
This study addresses the epistemological crisis in contemporary Islamic education, characterized by the dominance of cognitive formalism that reduces literacy to technical and measurable competencies while neglecting its spiritual and intellectual dimensions. Existing global scholarship on literacy and Islamic education largely positions pesantren traditions, particularly bandongan and sorogan, as sociocultural phenomena rather than as sources of epistemological theory. This indicates a significant theoretical gap in understanding how these practices function as systems of knowledge formation. This research aims to reconstruct Islamic literacy by conceptualizing bandongan and sorogan as epistemic practices. Employing a conceptual-normative literature review with epistemological and pedagogical approaches, the study analyzes classical Islamic texts, contemporary educational theories, and relevant policy documents. The analysis is conducted through systematic literature mapping, conceptual coding, and comparative epistemological interpretation. The findings reveal that bandongan and sorogan constitute integrated epistemological systems that combine textual authority, sanad-based knowledge transmission, and spiritual discipline (riyāḍah) in shaping the scholarly reasoning of santri. These practices operate not merely as instructional methods but as coherent frameworks that unify intellectual rigor and ethical formation. The novelty of this study lies in reframing traditional pesantren pedagogies as epistemic practices, thereby positioning them as a theoretical contribution to global literacy discourse. The study implies that integrating these traditional epistemic elements into modern educational systems can provide a more holistic model of literacy that bridges the divide between knowledge, ethics, and spirituality. Keywords: Islamic epistemology; traditional literacy; bandongan; sorogan; Islamic education